Spontaneously metastasizing rat sarcomas LW13K2 and RPS: assessment by the immunogenetic test of malignancy, in vitro behaviour and karyology - Veselý, P; Melezínková, H; Krenová, D; Kren, V; Matousková, E; Chaloupková, A (Folia biologica, 1989)
Populations of LW13K2 sarcoma derivatives were compared for their malignancy, patterns of cell behaviour in vitro (dynamic morphology and migration) and karyological pattern. The following tumour cell populations were used: the original LW13K2 sarcoma from inbred LEW/CUB rats, RPS sarcoma derived from it by neoplastic progression, four cell populations isolated in vitro from metastases of a syngeneic LEW-CUB strain rat with RPS tumour and four neoplastic cell populations isolated from spontaneous metastases shed by RPS sarcoma in allogeneic rats, differing from LEW/CUB in weak alloantigenic loci. Although RPS tumour did not grow progressively in MHC-different recipients (while the original LW13K2 tumour did), it grew progressively and metastasized in all groups of non-MHC allogeneic recipients. Parallel with the metastatic potential patterns of in vitro behaviour, such as an increased incidence of the quasi-stellate morphotype at slightly acid culture conditions endowed with enhanced changeability of the cell shape and migrational activity, were found. Cytogenetic analysis demonstrated rather stable chromosomal patterns over the cascade of neoplastic progression from LW13K2 sarcoma over RPS sarcoma to freshly isolated metastases. This indicated that the apparent neoplastic progression observed in the cell populations derived from LW13K2 sarcoma is with high probability not due to the selection at the chromosomal level.
Keywords: Cell Division; Tumor Cells, Cultured; Rats, Inbred Lew; krysa rodu Rattus; zvířata; experimentální sarkom; nádorové buňky kultivované; Neoplasm Metastasis; metastázy nádorů; chromozomální aberace; staging nádorů; pohyb buněk; Chromosome Aberrations; Cell Movement; potkani inbrední LEW; Rats; Neoplasm Staging; Animals; Sarcoma, Experimental; buněčné dělení